2006
DOI: 10.3892/ijo.29.5.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of RNAi-mediated Smad4 silencing on growth and apoptosis of human rhabdomyosarcoma cells

Abstract: Abstract. Transforming growth factor-ß (TGF-ß) signals through membrane-bound heteromeric serine/threonine kinase receptors. Upon ligand binding, TGF-ß activates intracellular Smad proteins and regulates proliferation and apoptosis in various cell types. To demonstrate the effects of TGF-ß/Smad signal on growth and apoptosis of human embryonal rhabdomyosarcoma (RMS) cells, a strategy of RNAi-mediated 'gene silencing' of Smad4 was used to interrupt endogenous TGF-ß/Smad signaling in an RMS cell line, RD, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…A simultaneous knockdown of Smad2, Smad3 and Smad4 proteins in human HaCaT keratinocyte cells, affected TGF-b-dependent responses in invasion, wound healing and apoptosis (Jazag et al, 2005). RNAi-mediated Smad4 silencing suppressed growth significantly and induced apoptosis of human rhabdomyosarcoma cells (Ye et al, 2006). A knockdown of Smad4 in MDA-MB-231 breast cancer cells, using shRNA-expressing vectors inhibited bone metastasis in nude mice and increased survival (Deckers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A simultaneous knockdown of Smad2, Smad3 and Smad4 proteins in human HaCaT keratinocyte cells, affected TGF-b-dependent responses in invasion, wound healing and apoptosis (Jazag et al, 2005). RNAi-mediated Smad4 silencing suppressed growth significantly and induced apoptosis of human rhabdomyosarcoma cells (Ye et al, 2006). A knockdown of Smad4 in MDA-MB-231 breast cancer cells, using shRNA-expressing vectors inhibited bone metastasis in nude mice and increased survival (Deckers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Smad4-siRNA Reverses EMT in Hepatocytes in Vitro-To demonstrate the central role of the TGF-␤1/Smad signal on EMT induction, siRNA technology was used for smad4 gene silencing in both primary and AML12 hepatocytes (24,25). The efficiency of siRNA transfection and resultant smad4 gene silencing in primary and AML12 hepatocytes was evaluated by IP, qRT-PCR, and IF.…”
Section: Tgf-␤1 Induces Snail-1 and Smad4 Activation In Hepatocytes-smentioning
confidence: 99%
“…Moreover, TGF-β1 treatment can partially counteract the effect of Smad4 shRNA in growth inhibition and apoptosis induction [9] . All of these findings suggest that the TGF-β1/Smad4 signaling pathway plays very important roles in RMS tumorigenesis and progression, and as such, may be a good target for RMS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that cells of the human ERMS cell line RD exhibit autocrine TGF-β1 signaling and overexpress TβR-I, TβR-II and the downstream Smads 2, 3 and 4 [8] . Importantly, exogenous TGF-β1 can partially counteract the effect of Smad4 knockdown by RNA interference [9] . These results suggest that TGF-β1 may be a novel therapeutic target for RMS treatment.…”
mentioning
confidence: 99%